THE IMPACT OF RISK-BASED CAPITAL (RBC) RATIO ON THE FINANCIAL PERFORMANCE OF INSURANCE COMPANIES IN INDONESIA - Mukhtaruddin (GREET, 2024)
This study investigates the impact of the Risk-Based Capital (RBC) ratio on the financial performance of insurance companies in Indonesia, an emerging market where regulatory solvency requirements play a critical role in maintaining industry stability. Using a sample of 30 insurance firms listed in Indonesia during the 2018–2023 period, the study applies descriptive statistics, Pearson correlation, and multiple regression analysis to examine the relationship between RBC ratio, return on assets (ROA), and return on equity (ROE). The results reveal a significant positive relationship between the RBC ratio and financial performance, indicating that firms with higher solvency margins are more likely to generate stronger profitability and demonstrate operational resilience. Furthermore, the findings highlight heterogeneity across firm size, with large insurers benefiting more consistently from strong RBC positions compared to smaller firms, which remain vulnerable to market volatility. This study contributes to the literature by providing empirical evidence from Indonesia, where limited research has addressed the direct impact of solvency regulations on firm performance. The results offer practical implications for regulators, suggesting that continuous monitoring and stricter enforcement of RBC requirements are essential to safeguard market stability, while insurance companies should optimize capital structures to enhance both compliance and profitability.